Mycological Diversity Description I - Jadson Diogo Pereira Bezerra; Alexandre Reis Machado; André Luiz Firmino; André Wilson Campos Rosado; Carlos Alberto Fragoso de Souza; Cristina Maria de Souza-Motta; Karla Torres Lins de Sousa Freire; Laura Mesquita Paiva; Oliane Maria Correia Magalhães; Olinto Liparini Pereira; Pedro W. Crous; Thays Gabrielle Lins de Oliveira; et al. (Acta Botânica Brasílica, 2018)
ABSTRACT Here, Quambalaria fabacearum and Neopestalotiopsis brasiliensis are introduced as new species from Brazil, isolated as endophyte from Mimosa tenuiflora and causing post-harvest rot disease on fruits of Psidium guajava, respectively. Diaporthe inconspicua is emended to include a more detailed morphological description. Neopestalotiopsis egyptiaca is reported as new to the Americas and as causing post-harvest rot disease on fruits of Psidium guajava, while Umbelopsis isabellina is reported as endophyte.